Foreign policy of England in 1485–1558 and the political geography of the English diplomatic representation - Mazarchuk, Dmitry V. (Journal of the Belarusian State University. History, 2023)
In order to study the political geography of the English diplomatic mission during the Italian wars, the article analysis quantitative data from the prosopographic corpus of English diplomats in 1485–1558. Article presents the results of the analysis of the political-geographical distribution of the English diplomatic missions in 1485–1558. As a result of the analysis, three main political and geographical directions of the diplomatic activity of British diplomacy were identified: France, the possessions of the Habsburgs, and Scotland. One of the factors of diplomatic activity in the first and second directions is their confrontation as the central elements of the two military-political blocs during the Italian wars. The dynamics of diplomatic relations in the Italian direction was also due to its changing significance during the wars of 1494–1559. It is concluded that during the reign of the first and middle Tudors, the practice of sending resident ambassadors formed a hierarchy that coincided with the geography of distribution of the model of resident diplomatic representation in Western Europe. The main elements of the hierarchy (in descending order of importance): Venice and Rome; great powers (France, Spain, possessions of the Habsburgs), other states. The author also came to the conclusion that the geography of the English diplomatic mission at the end of the 15th – the first half of the 16th century changed depending on the changing priorities of British foreign policy. In particular, the influence of the Reformation on such changes was revealed: the activation of the German direction in the 1530s, a break in diplomatic relations with the Papacy after 1533. During the Italian wars, England played a subordinate role, manifested in the support of one of the two main participants in the conflict. The aim of most of the English embassies of this period was the states of the Habsburgs and Valois, which indirectly confirms the secondary importance of England during the period of the first and middle Tudors in the interstate relations of the early Modern period.
Keywords: England; Tudors; Italian wars; diplomacy; diplomatic history; history of the international relations; prosopography